Sexual politics in selected Cuyunon folk songs. - Cabrestante, Ma. Anthea A.
The purpose of this study is to examine the sexual political condition of Cuyunon women as portrayed in the folk songs of Cuyo, Palawan. As one of the studies that examine Philippine folk literature using a feminist lens, this study seeks to uncover how deeply ingrained the patriarchal norms and values are in the Cuyunon and Palaweño society through a sexual political analysis of the Cuyunon folk songs. The analysis of the texts has two parts: the first part analyzes the binary oppositions of gender roles present in the songs, it is found out that most of the songs portray traditional gender roles for men and women, and that the perpetuation of gender roles and stereotypes play a big role in the oppression of women. This study has concluded that according to the Cuyunon folk songs, Cuyunon women are only temporarily empowered during the courtship phase, but they still occupy and inferior position in the sexual politics of their society. Furthermore, this study has also concluded that aside from reflecting patriarchal culture of the Cuyunon society, the Cuyunon folk songs are tools for the propagation and normalization of patriarchal culture as they are sang and heard again and again.